Inhibitory effects of phenolic compounds of rice straw formed by saccharification during ethanol fermentation by Pichia stipitis. (November 2017) - Wang, Xiahui; Tsang, Yiu Fai; Li, Yuhao; Ma, Xiubing; Cui, Shouqing; Zhang, Tian-Ao; Hu, Jiajun; Gao, Min-Tian
Graphical abstract: Highlights: Phenolic acids (PAs) were the major factors affecting ethanol fermentation with rice straw. Free PAs strongly inhibited ethanol fermentation. Conjugated PAs weakly inhibited ethanol fermentation. Flow cytometry assay showed that the inhibition resulted from damage to cell membrane. Integrated processes that include ethanol and PAs for the low-cost production of ethanol were discussed. Abstract: In this study, it was found that the type of phenolic acids derived from rice straw was the major factor affecting ethanol fermentation by Pichia stipitis . The aim of this study was to investigate the inhibitory effect of phenolic acids on ethanol fermentation with rice straw. Different cellulases produced different ratios of free phenolic acids to soluble conjugated phenolic acids, resulting in different fermentation efficiencies. Free phenolic acids exhibited much higher inhibitory effect than conjugated phenolic acids. The flow cytometry results indicated that the damage to cell membranes was the primary mechanism of inhibition of ethanol fermentation by phenolic acids. The removal of free phenolic acids from the hydrolysates increased ethanol productivity by 2.0-fold, indicating that the free phenolic acids would be the major inhibitors formed during saccharification. The integrated process for ethanol and phenolic acids may constitute a new strategy for the production of low-cost ethanol.